The Impact of Race in Male Breast Cancer Treatment and Outcome in the United States: A Population-Based Analysis of 4,279 Patients - Jacob Y. Shin; Lisa A. Kachnic; Ariel E. Hirsch (International Journal of Breast Cancer)
The purpose of this study is to compare the racial differences in treatment and overall survival (OS) of male breast cancer (MBC) patients. Data were extracted from the NCI SEER database that included population-based registries from 1988 to 2010 and analyzed using SPSS 20.0. 4,279 MBC patients were identified. 3,266 (76.3%) patients were White, 552 (12.9%) Black, 246 (5.7%) Hispanic, and 215 (5.0%) Asian. Black patients were more likely to be diagnosed at younger age (P<0.001), have advanced stage disease (P=0.001), and be unmarried (P<0.001) and less likely to undergo lymph node dissection (P=0.006). When stratified by stage, there was no difference in receipt of primary treatment by race. The 5-year OS for White, Black, Hispanic, and Asian races was 73.8%, 66.3%, 74.0%, and 85.3% (P<0.001). This significant worse 5-year OS for Blacks persisted regardless of age, stage II or III disease, and grade 2 or 3 disease. On multivariate analysis, Black race was a significant independent prognostic factor for worse OS. Blacks were less likely to receive lymph node dissection of which patients may derive benefit, though we did not observe receipt of primary treatment, after stratifying for disease stage, to be an underlying factor contributing to racial outcome differences.